Historical review of Lynch syndrome - Wolf, Andrew I.; Buchanan, Adam H.; Farkas, Linda M. (Journal of Coloproctology, 2013)
Lynch syndrome was formerly known as Hereditary Nonpolyposis Colorectal Cancer. Currently, these two nomenclatures each have their unique definitions and are no longer used interchangeably. The history of hereditary nonpolyposis colorectal cancer was first recognized formally in the literature by Henry Lynch in 1967. With advances of molecular genetics, there has been a transformation from clinical phenotype to genotype diagnostics. This has led to the ability to diagnose affected patients before they manifest with cancer, and therefore allow preventative surveillance strategies. Genotype diagnostics has shown a difference in penetrance of different cancer risks dependent on the gene containing the mutation. Surgery is recommended as prevention for some cancers; for others they are reserved for once cancer is noted. Various surveillance strategies are recommended dependent on the relative risk of cancer and the ability to intervene with surgery to impact on survival. Risk reduction through aspirin has shown some recent promise, and continues to be studied.
Keywords: Lynch syndrome; Hereditary nonpolyposis colorectal cancer; Colorectal cancer; Amsterdam criteria; Bethesda criteria; Microsatellite instability: MSI; Immunohistochemistry: IHC; Familial cancer; Muir-Torre syndrome; Turcot syndrome; Family X; Mismatch repair